Pelatihan Digital Marketing Dalam Pemberdayaan UMKM Desa Lingga Tiga - Juledi, Angga Putra; Harahap, Syaiful Zuhri; Nasution, Marnis; Irmayani, Deci (JURNAL PKM IKA BINA EN PABOLO, 2024)
The development of the digital world which is increasingly spreading provides convenience in various fields, one of which is in marketing. By utilizing the development of the digital world in the field of marketing, it is implemented to help UMKM UMKM who need tools to promote their products. Lingga Tiga Village, which is one of the villages in Labuhanbatu Regency, needs more promotion for UMKM activities. Seeing this, Digital Marketing Training was held which aims to empower UMKM in Lingga Tiga so that they can promote their products to the wider world and increase their activities.